Current view of the inhibitor protein cyclin-dependent kinase р16, р27 and their role in the cell cycle - A. K. Aleksandrova; V. A. Smolynnikova (Кубанский научный медицинский вестник, 2016)
Violations of the cell cycle have their own characteristics in the skin lesions. The greatest attention is paid to the research of cancers, whereas benign tumors of the skin insufficiently studied. The article presents data on the characteristics of protein expression of cyclin dependent kinase inhibitor p16, p27, and their role in the cell cycle and oncogenesis.